Science, technology, and society - Mcginn, Robert E. (Singapore : Pearson education asia, 1991)
Includes bibliographical references and index
Keywords: Science -- Study and teaching; Technology -- Study and teaching; Science -- Social aspects; Technology -- Social aspects